1998
DOI: 10.1093/pasj/50.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamical Simulation of Clusters of Galaxies in X-Ray, mm, and submm Bands: Determination of Peculiar Velocity and the Hubble Constant

Abstract: We have performed a series of simulations of clusters of galaxies on the basis of the smoothed particle hydrodynamics technique in a spatially-flat cold dark matter universe with Ω = 0.3, λ = 0.7, and H 0 = 70km/s/Mpc as one of the most successful representative cosmological scenarios. In particular, we focus on the Sunyaev-Zel'dovich effect in submm and mm bands, and estimate the reliability of the estimates of the global Hubble constant H 0 and the peculiar velocity of clusters v r . Our simulations indicate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
4
33
1
Order By: Relevance
“…In fact, there have been several previous attempts toward the same goal, mainly utilizing numerically simulated galaxy clusters (Inagaki et al 1995;Yoshikawa et al 1998;Sulkanen 1999). They concluded that departure from sphericity and isothermality of clusters results in f H 6 ¼ 1, but after averaging over a sample the systematic errors are relatively small, jh f H i À 1j % 5%.…”
Section: Estimating H 0 From the Sze In The Spherical Isothermal -Modelmentioning
confidence: 99%
“…In fact, there have been several previous attempts toward the same goal, mainly utilizing numerically simulated galaxy clusters (Inagaki et al 1995;Yoshikawa et al 1998;Sulkanen 1999). They concluded that departure from sphericity and isothermality of clusters results in f H 6 ¼ 1, but after averaging over a sample the systematic errors are relatively small, jh f H i À 1j % 5%.…”
Section: Estimating H 0 From the Sze In The Spherical Isothermal -Modelmentioning
confidence: 99%
“…In fact, our latest hydrodynamical simulations (Yoshikawa, Jing, & Suto 2000) show that the mass-and emission-weighted temperatures of simulated clusters satisfy the above relation with c \ 1.2 and 1.6, respectively. Further details of the temperature-mass relation and its nonisothermal e †ect are discussed in , Yoshikawa, Itoh, & Suto (1998), , and Yoshikawa & Suto (1999). We compute the ratio of the * vir , mean cluster density to the mean density of the universe at that epoch, using the formulae for the spherical collapse model presented in Kitayama & Suto (1996).…”
Section: Modeling the Two-point Correlation Functions Of X-ray Clustersmentioning
confidence: 99%
“…This angular diameter distance is translated into and km s timates still have fairly large errors compared with those from optical observations, it is encouraging that they fit in a reasonable range, and we expect to improve the estimates by observing the cluster again (hopefully in much better weather conditions). Then it will be feasible to separate the kinematic and thermal SZ effects by a simultaneous fit to the 21 and 350 GHz data, which will yield an estimate of the peculiar velocity of the cluster (Rephaeli & Lahav 1991;Yoshikawa et al 1998;Birkinshaw 1999). …”
Section: The 350 Ghz Observation With Jcmt/scubamentioning
confidence: 99%
“…In the above discussion, we have neglected several issues that, in principle, could affect our interpretation of the detection of the SZ signal from the cluster, including a possible variability of the central point source, a nonsphericity and nonisothermality (Yoshikawa et al 1998;Yoshikawa & Suto 1999), a cooling flow (Fabian 1994;Allen 1998;Allen & Fabian 1998), a contribution of submillimeter dust (Lamarre et al 1998;Edge et al 1999), unresolved lensed sources, and a peculiar velocity of the cluster. To some extent, these would definitely contribute to putting additional uncertainties on the best-fit parameters of the cluster.…”
Section: The 350 Ghz Observation With Jcmt/scubamentioning
confidence: 99%
See 1 more Smart Citation